PELAKSANAAN INKLUSI DI SEKOLAH DASAR NEGERI 14 PAKAN SINAYAN PAYAKUMBUH (Deskriptif Kualitatif) - Winda Quida Sari (Universitas Negeri Padang, 2012)
Issues raised in this study is the implementation of Inclusion in State Primary School Feeding Sinayan Payakumbuh 14, to reveal how the implementation of inclusion in the primary schools feeding 14 Sinayan Payakumbuh, which discusses how to identify children who will attend SDN 14 Feed Sinayan Payakumbuh, curriculum that is in use school , responsibilities and roles of teachers and facilities in schools. The results showed that the implementation of inclusion in the SDN 14 was not happened with the maximum, because the implementation of the identification of GPK only do the majority of children, the curriculum is in use KTSP, GPK provides services only in class 1 only and do not use the program, PPI. Classroom teachers to teach without the use of media and just use the lecture method, lesson plans made ​​by the classroom teacher is issued if there is a survey of department and principals, the local infrastructure space so dense that in a bench seat 4 and 3 children, spatial class is irregular, ABK seat separated from her friends and learning is not based on the program made ​​by the teacher. Based on the conclusipons and results of research that the implementation of inclusion in the SDN 14 is not maximized and the need to enhance cooperation between the school, consisting of classroom teachers, special tutor, and teachers in the study so that goals can be achieved with a good education.